The Burr X Pareto Distribution: Properties, applications and VaR estimation - Mustafa Ç. Korkmaz; Emrah Altun; Haitham M. Yousof; Ahmed Z. Afify; Saralees Nadarajah (Journal of Risk and Financial Management, 2018)
In this paper, a new three-parameter Pareto distribution is introduced and studied. We discuss various mathematical and statistical properties of the new model. Some estimation methods of the model parameters are performed. Moreover, the peaks-over-threshold method is used to estimate Value-at-Risk (VaR) by means of the proposed distribution. We compare the distribution with a few other models to show its versatility in modelling data with heavy tails. VaR estimation with the Burr X Pareto distribution is presented using time series data, and the new model could be considered as an alternative VaR model against the generalized Pareto model for financial institutions.
Keywords: 330; Burr X distribution; Pareto distribution; maximum likelihood estimation; heavy tail distribution; value-at-risk